Pengaruh Kepemilikan Manajerial, Profitabilitas, Dan Leverage Terhadap Kebijakan Dividen Dengan Likuiditas Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2024 - Risda Maysari Lubis; Muhammad Arief; Rizki Fillhayati Rambe (Jurnal Manajemen Dan Akuntansi Medan, 2025)
This research aims to determine managerial ownership, profitability, and leverage on dividend policy with liquidity as a moderating variable in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2015-2024. The sample selection method used is purposive sampling. The total observations in this research were 100 samples with 10 years of observation consisting of 10 companies. The data analysis technique used in this research is multiple linear regression analysis and moderation analysis.Simultaneous test results show that managerial ownership, profitability, and leverage affect dividend policy together. Partial test results show that profitability, managerial ownership, and leverage affect dividend policy. The moderation test results show that liquidity is able to moderate and strengthen the effect of profitability on dividend policy, while liquidity is not able to moderate and weaken the effect of managerial ownership and leverage on dividend policy.